Visible Light Communications Based on CDMA Technology - Qiu, Yang; Chen, Shuyi; Chen, Hsiao-Hwa; Meng, Weixiao (IEEE wireless communications, 2018)
VLC can perform the functions of communications and lighting simultaneously, which is expected to be an important part of next-generation wireless communications. Compared to traditional RF wireless communications, VLC offers many salient features, such as its operation on unlicensed visible light spectra, its support of high communication rates, and its immunity against electromagnetic interferences. In this article, we focus on code division multiple access techniques used in VLC systems and discuss different application scenarios for VLC-CDMA technologies. In particular, two types of VLC-CDMA systems will be identified, i.e., unipolar codes and bipolar codes based VLC-CDMA systems, whose performances will be analyzed and compared explicitly.